Self-harm, suicidal behaviours, and cyberbullying in children and young people: systematic review - John, A; Glendenning, AC; Marchant, A; Montgomery, P; Stewart, A; Wood, S; Lloyd, K; Hawton, K (JMIR Publications, 2018)
Background: Given the concerns about bullying via electronic communication in children and young people and its possible contribution to self-harm, we have reviewed the evidence for associations between cyberbullying involvement and self-harm or suicidal behaviors (such as suicidal ideation, suicide plans, and suicide attempts) in children and young people. Objective: The aim of this study was to systematically review the current evidence examining the association between cyberbullying involvement as victim or perpetrator and self-harm and suicidal behaviors in children and young people (younger than 25 years), and where possible, to meta-analyze data on the associations. Methods: An electronic literature search was conducted for all studies published between January 1, 1996, and February 3, 2017, across sources, including MEDLINE, Cochrane, and PsycINFO. Articles were included if the study examined any association between cyberbullying involvement and self-harm or suicidal behaviors and reported empirical data in a sample aged under 25 years. Quality of included papers was assessed and data were extracted. Meta-analyses of data were conducted. Results: A total of 33 eligible articles from 26 independent studies were included, covering a population of 156,384 children and young people. A total of 25 articles (20 independent studies, n=115,056) identified associations (negative influences) between cybervictimization and self-harm or suicidal behaviors or between perpetrating cyberbullying and suicidal behaviors. Three additional studies, in which the cyberbullying, self-harm, or suicidal behaviors measures had been combined with other measures (such as traditional bullying and mental health problems), also showed negative influences (n=44,526). A total of 5 studies showed no significant associations (n=5646). Meta-analyses, producing odds ratios (ORs) as a summary measure of effect size (eg, ratio of the odds of cyber victims who have experienced SH vs nonvictims who have experienced SH), showed that, compared with nonvictims, those who have experienced cybervictimization were OR 2.35 (95% CI 1.65-3.34) times as likely to self-harm, OR 2.10 (95% CI 1.73-2.55) times as likely to exhibit suicidal behaviors, OR 2.57 (95% CI 1.69-3.90) times more likely to attempt suicide, and OR 2.15 (95% CI 1.70-2.71) times more likely to have suicidal thoughts. Cyberbullying perpetrators were OR 1.21 (95% CI 1.02-1.44) times more likely to exhibit suicidal behaviors and OR 1.23 (95% CI 1.10-1.37) times more likely to experience suicidal ideation than nonperpetrators. Conclusions: Victims of cyberbullying are at a greater risk than nonvictims of both self-harm and suicidal behaviors. To a lesser extent, perpetrators of cyberbullying are at risk of suicidal behaviors and suicidal ideation when compared with nonperpetrators. Policy makers and schools should prioritize the inclusion of cyberbullying involvement in programs to prevent traditional bullying. Type of cyberbullying involvement, frequency, and gender should be assessed in future studies.